THE POTENTIAL ROLE OF PUBLIC-PRIVATE PARTNERSHIPS IN IMPROVING THE FOOD AND NUTRITION SECURITY IN WEST PAPUA - Usfar, Avita Aliza; Sudibya, Arienta; Hurulean, Ferdinandus; Heatubun, Charlie (Agricultural Socio-Economics Journal, 2024)
The study aims to stimulate the potential of a Public-Private Partnership (PPP) in West Papua province, which ranks 33rd (out of 34) on the Indonesian Food and Nutrition Security (FNS) Index and where stunting is a public health challenge. The authors analyzed the potential by using FNS Indicators and examining the results of discussions with the stakeholders. We propose to focus interventions on the provision of food for vulnerable individuals, behavioral change communication to improve the consumption of healthy local food, improvement of the knowledge of mothers and other household members about food and nutrition, the promotion and reinforcement of exclusive breastfeeding for children below six months, the improvement of access to clean water and latrines, the improvement of access to preventive and health care services by providing one nutritionist per village, and the provision of iron and folic-acid tablets to pregnant women and adolescent girls. A multi-stakeholder effort should be put in place, led by the provincial government, comprising representatives from the offices of public works, health, education, and social affairs. The network should involve the 36 private companies based in the area. Educational materials could be reproduced by the printing companies and distributed by the construction, fishing, and timber companies. The government of West Papua should identify food and nutrition as a priority concern and widen its existing PPP activities beyond Corporate Social Responsibility.